2002
DOI: 10.1080/140174302762659085
|View full text |Cite
|
Sign up to set email alerts
|

Release Patterns of Pregnancy Associated Plasma Protein A (PAPP-A) in Patients with Acute Coronary Syndromes

Abstract: PAPP-A is an additional marker for ACS, but does not seem to be a useful early marker for acute myocardial infarction (AMI). The possible clinical utility of PAPP-A calls for extensive studies of chest pain patients using serial sampling combined with short- and long-term outcome studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 8 publications
2
36
0
3
Order By: Relevance
“…It was suggested that measurement of PAPP-A could be used as an additional diagnostic and prognostic biomarker in patients presenting with chest pain. 209 Early studies showed that there are more patterns in patients with chest pain and it was suggested that it might not prove to be a useful early biomarker for diagnosis 210 but does appear to be prognostic. 211,212 Elevations of PAPP-A were reported to correlate with the extent of both coronary 213 and peripheral 214 vascular disease.…”
Section: Pregnancy-associated Plasma Protein Amentioning
confidence: 99%
“…It was suggested that measurement of PAPP-A could be used as an additional diagnostic and prognostic biomarker in patients presenting with chest pain. 209 Early studies showed that there are more patterns in patients with chest pain and it was suggested that it might not prove to be a useful early biomarker for diagnosis 210 but does appear to be prognostic. 211,212 Elevations of PAPP-A were reported to correlate with the extent of both coronary 213 and peripheral 214 vascular disease.…”
Section: Pregnancy-associated Plasma Protein Amentioning
confidence: 99%
“…Finally, our results show that the molecular size of pregnancy-related PAPP-A is larger than that of ACSrelated PAPP-A, which further demonstrates that ACSrelated PAPP-A differs from pregnancy-related PAPP-A. In ACS, PAPP-A concentrations seldom exceed 30 mIU/L, which is equivalent to ϳ10 g/L (16,18 ). Such low concentrations make it difficult to detect ACS-related PAPP-A directly from blood samples by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western blot analyses.…”
Section: Discussionmentioning
confidence: 69%
“…Samples were obtained from eight patients, four males [mean (SD) age, 63 (13) years] and four females [72 (16) years] with typical ST-elevation MI, at admission; at 1, 2, 4, 6, 24, 48 h afterward; and at discharge. In addition, three first-trimester serum samples (gestational ages, 9, 10, and 11 weeks) and one third-trimester serum sample (gestational age, 33 weeks) were included.…”
Section: Serum Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…oraz Schoos i wsp. wykazali natomiast, że wzrost PAPP-A różni się pomiędzy pacjentami z OZW, a okno diagnostyczne mieści się w przedziale 2-30 godzin od początku bólu [26,27]. Lund i wsp.…”
Section: Wartość Diagnostyczna Osoczowego Białka Typu a Związanego Z unclassified